Physiological and psychological effects of weight loss-induced stress before a competition in senior wrestlers - Okudan, Bilal; Isik, Ozkan; Akyurek, Zeynep; Karakullukcu, Omur Fatih; Talaghir, Laurentiu-Gabriel; Nanu, Liliana (Frontiers in Psychology, 2025)
BackgroundIt is known that stress occurring through/against a phenomenon will have physiological and psychological effects on the human organism. Therefore, this research aimed to determine the physiological and psychological effects of weight loss-induced stress before a competition in senior wrestlers.MethodsThis cross-sectional study used a purposeful sampling method to select participants. Two hundred and forty-three wrestlers participated in the study voluntarily. The perceived stress scale and athlete weight loss methodology and effects scale were used to determine the physiological and psychological effects of weight loss-induced stress. Independent samples t-test, One-way ANOVA, Pearson correlation analysis, and linear regression analysis were used to analyze normally distributed data.ResultsThere was no statistical difference in the wrestlers’ body weight loss percentages, stress levels, and weight loss methods and effects sub-dimensions according to their gender and wrestling styles (p > 0.05). Despite this, there was a statistical difference in wrestlers’ stress levels, ergogenic aids sub-dimension from weight loss methods, and psychological effect levels according to body weight loss percentages (p < 0.05). Additionally, there was a positive relationship between the body weight loss percentages of wrestlers with their stress levels (r: 0.461) and psychological effects (r: 0.240). Furthermore, there was a positive relationship between the stress levels of wrestlers with the average physiological (r: 0.298) and psychological (r: 0.508) effects. According to these results, it was determined that as the body weight loss percentages of wrestlers increased, their stress levels and the psychological effects they were exposed to would increase. It was also determined that as the stress level of wrestlers increased, the physiological and psychological effects they were exposed to would increase the weight loss-induced stress levels of wrestlers positively predicted their exposure to physiological and psychological effects at 8.5% (Adj. R2 = 0.085) and 25.8% (Adj. R2 = 0.258), respectively.ConclusionIt was determined that as the percentage of body weight loss increases in wrestlers, the stress level will also increase and the stress level increases, the physiological and psychological effects will also increase. It is thought that weight loss-induced stress has both physiological and psychological effects on wrestlers and may reduce their athletic performance.